Development of the Life Roles Inventory-Values Scale - Macnab, Donald; Fitzsimmons, George; Casserly, Catherine (Canadian Journal of Counselling and Psychotherapy, 2011)
This article outlines the procedures involved in the construction of the Canadian version of the Life Roles Inventory—Values Scale (CanadianWork Importance Study, 1986). The Values Scale is the product of the development of Canadian and international teams of psychologists. The Canadian version has been developed in both French and English. The article outlines studies of the reliability (internal consistency, test-retest, and alternate form), and validity (construct, convergent, discriminant, and concurrent) of the inventory.